2020
DOI: 10.1016/j.jhepr.2020.100149
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the patient with acute severe autoimmune hepatitis

Abstract: Autoimmune hepatitis is associated with varied clinical presentations and natural history, as well as somewhat unpredictable treatment responses. Understanding how to stratify patients who require further escalation of therapy will help clinicians manage these patients. The presentation of acute severe autoimmune hepatitis (AS-AIH) is relatively uncommon, although its prevalence is potentially greater than currently perceived. Previous studies consist of small retrospective single-centre series and are not dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 149 publications
(339 reference statements)
1
38
0
7
Order By: Relevance
“…Other work-up including anticentromere B antibodies, antichromatin antibodies, anti-Jo-1, anti-RNP antibodies, anti-scleroderma 70 antibodies, Smith antibodies, Sjogren anti-SS-A and Sjogren anti-SS-B was negative. Our patient was taking fenofibrate which has been associated with AIH, but he had been taking it for more than 3 years [2] . The patient was diagnosed with AIH-PBC overlap syndrome triggered by COVID-19 (given the sequence of events with COVID-19 infection followed by the onset of fatigue/arthralgias, laboratory evidence of hyperferritinemia, elevated liver enzymes (AST/ALT/GGT), hypergammaglobulinemia, anti-smooth muscle antibody, anti-mitochondrial antibody and anti-double-stranded DNA antibodies).…”
Section: Case Descriptionmentioning
confidence: 90%
See 1 more Smart Citation
“…Other work-up including anticentromere B antibodies, antichromatin antibodies, anti-Jo-1, anti-RNP antibodies, anti-scleroderma 70 antibodies, Smith antibodies, Sjogren anti-SS-A and Sjogren anti-SS-B was negative. Our patient was taking fenofibrate which has been associated with AIH, but he had been taking it for more than 3 years [2] . The patient was diagnosed with AIH-PBC overlap syndrome triggered by COVID-19 (given the sequence of events with COVID-19 infection followed by the onset of fatigue/arthralgias, laboratory evidence of hyperferritinemia, elevated liver enzymes (AST/ALT/GGT), hypergammaglobulinemia, anti-smooth muscle antibody, anti-mitochondrial antibody and anti-double-stranded DNA antibodies).…”
Section: Case Descriptionmentioning
confidence: 90%
“…The exact mechanisms leading to AIH-PBC overlap syndrome are not fully understood. In genetically predisposed individuals, viruses and drugs have been suggested as triggering agents for the autoimmune disease [2] . We report a case of AIH-PBC overlap syndrome triggered by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…AIH presenting as severe acute disease or fulminant liver failure remain challenging and require early consideration for liver transplant [ 129 , 132 , 221 ]. In fulminant liver failure, defined by the presence of encephalopathy, a short trial of corticosteroids has rarely shown to be beneficial, and patients should undergo urgent liver transplantation [ 129 , 132 ].…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…Firstly, we need to bear in mind that a non-response to corticosteroids may be due to the severity of liver injury but could also result from an incorrect diagnosis. 7 The diagnosis of AS-AIH can be challenging as the International Autoimmune Hepatitis Group (IAIHG) criteria that are commonly used have never been validated in this particular setting. A liver biopsy is indicated but is not always performed, and sometimes when histology is available, it shows massive necrosis that is difficult to interpret and can correspond to acute liver failure (ALF) of indeterminate etiology.…”
Section: To the Editormentioning
confidence: 99%